Analysis strategy of Sheep farm development in Bondowoso Regency - Muhamad Agung Taufiqurrachman; Usman Ali; Inggit Kentjonowaty (Politeknik Negeri Jember, 2023)
The sheep population in Bondowoso Regency increases every year, but this number cannot meet the demand for sheep meat. Therefore, this study was conducted to analyze the internal and external factors affecting sheep farming in Bondowoso Regency, as well as to determine the strategies that should be carried out according to experts and analyzed using the Analysis Hierarchy Process (AHP). This study used purposive sampling, where the number of respondents was 30 sheep farmers. Furthermore, questionnaires were distributed to 2 experts in the field of animal husbandry. Questionnaires from farmers were processed using SWOT analysis and questionnaires from livestock experts were processed using AHP. The results of the SWOT analysis are that 50% of respondents are in Quadrant 1, 6.67% in Quadrant 2, 16.67% in Quadrant 3, and 26.67% in Quadrant 4. The conclusion of this study was based on SWOT analysis, 50% of sheep farmers in Bondowoso Regency are in a very favorable condition. Based on AHP, the most recommended variable was code V1,